Integrating hemodynamic analysis with traditional imaging in intracranial atherosclerotic stenosis: current status and future perspectives - Yin, Xulong; Yang, Rui; Li, Zhen; Wang, Hui; Fang, Qi (Frontiers in Neurology, 2025)
Intracranial atherosclerotic stenosis (ICAS) is a significant cause of ischemic stroke. Traditional imaging methods have their own advantages and disadvantages in the diagnosis of ICAS. Hemodynamic analysis technology, as a new technique and method based on conventional imaging examinations, when combined with traditional imaging, can more comprehensively assess the hemodynamic status of ICAS patients, providing a new direction for the diagnosis and research of ICAS. This review provides an overview of the traditional imaging techniques currently used to diagnose ICAS, including transcranial Doppler ultrasound (TCD), computed tomography angiography (CTA), magnetic resonance angiography (MRA), high-resolution magnetic resonance imaging, and digital subtraction angiography (DSA). The unique characteristics of each method are elaborated. In addition, examples of hemodynamic analysis applications based on these traditional imaging techniques are discussed. This article summarizes and reviews the prospects and limitations of ICAS hemodynamic analysis and proposes potential directions for future research. As a recently developed clinical evaluation method for ICAS, hemodynamic analysis techniques have demonstrated significant potential in various aspects of ICAS, including clinical diagnosis, etiological exploration, treatment selection, and recurrence prediction. It is hoped that the method of hemodynamic analysis will ultimately be incorporated into the treatment guidelines for ICAS patients, paving new ways for the diagnosis and treatment of ICAS.